MENUMBUHKAN NILAI-NILAI SOCIAL INTELLIGENCE SEBAGAI WUJUD HUMANISME PENDIDIKAN - Munib, Abdul (Universitas Islam Madura, 2014)
Education problem in this country do not only at education amount and relate to the quality of result of education by behind of the eye is still fail to view with some neighbouring state like Malaysia, Singapore, Thailand and Combodia, if we compared to with history of forming of Indonesian state. Processing of education in learning child only focused at preparation of passing the examination of certain ladder to other ladder form mentality mechanical learn, disregarding side of socio cultural learning life of society social around him. The Impact how to emerge children to their environment and their live that they will become superior. If aggrieving a few, hence, they will emerge to feel to be competed with, not ready to others excel themselves, what more tragic if this superior shall no longer on behalf of importance of acquirement of science, experience, attitude and value. However, more to hedonism life of the rising generation or student which flange to life of negativity. Hence which often happened is emerging hardness attitude literate community anarchism which often reported on at the mass media. Anarchism which tip at often the happening of fight between student without clear reason, but its impact always emerge victim of death without effect, even the victim do not know sudden what's going on jerked.